Effects of the fungus Pestalotiopsis maculans (Ascomycota: Amphisphaeriales) on the gametophytic development of the fern Lygodium venustum (Lygodiaceae) - Bejar, Julieta (2019)
Lygodium Sw. is the only genus of the family Lygodiaceae, with around 25 to 40 species inhabiting mostly tropical regions worldwide. In Argentina two species develop; one of them, L. venustum, grows in the Northeast of the country. Some species of Lygodium are invasive whereas medicinal uses have been reported for some taxa. As part of a project to ascertain on the reproductive biology of native ferns in Argentina, a fungus was found during in vitro spore culture of L. venustum. Dark brown spots and eruptive pustules were also observed in fertile leaves. Thus, emerged as objectives of this work: 1) to retrieve and identify the fungus from the sporophyte and from the spores cultures, 2) to inquire on the impact of the fungus on gametophyte generation, and 3) to perform experiments with untreated spores to demonstrate that the fungus is associated to the spores collected from infested sporophytes. Phytopathological techniques were applied in order to isolate the fungus and then to achieve monosporic cultures. The morpho-biometric features of the conidia corresponded with those of Pestalotiopsis maculans (Corda) Nag Raj [= Pestalotiopsis guepinii (Desm.) Steyaert] (Amphisphaeriales, Ascomycota). Re-inoculation of conidia on healthy gametophytes conducted to their necrosis and death. The percentages of spore germination were initially higher in unsterilized cultures, suggesting that disinfection protocol may have affected spore germination. This is the first report of Pestalotiopsis maculans on the sporophytes of Lygodium venustum. The information that emerges from our work could be useful for the biocontrol of other species of Lygodium, considered weeds in other regions of the world.